Molecular Evaluation of Enzalutamide Resistance in Prostate Cancer - AIRD, JOHN (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2020)
Prostate cancer is a leading cause of cancer related death in men. As prostate cancer cells are dependent on androgen receptor (AR) signalling for continued growth, anti-androgen therapy is initially effective in treating most patients with locally advanced or metastatic PCa. However, resistance to anti-androgen therapies inevitably develops in all patients leading to castration resistant prostate cancer (CRPC), which is currently incurable. In most cases of drug resistance, AR signalling is maintained despite castration levels of androgens. The molecular underpinnings for how this occurs and how it can be overcome have yet to be fully elucidated. Non-coding RNAs, initially thought to be redundant parts of the genome, are now known to be involved in the regulation of key cellular processes in human tumourigenesis and in the development of drug resistance. Long non-coding RNAs (lncRNAs) are non-coding RNAs > 200 nucleotides in length and over 100,000 have been identified in the human genome. Whether all these lncRNAs play a functional role in cellular biology and what that role may be, is still largely unknown. The objective of this study was to evaluate the molecular mechanisms underlying resistance to the anti-androgen enzalutamide in PCa. An isogenic cell line model with clones of varying resistance to enzalutamide was used. Microarray analysis was performed and differentially expressed lncRNAs and mRNAs identified. Six lncRNAs were validated by qPCR as being significantly overexpressed in enzalutamide resistant PCa cells - SPRY4-IT1, DPP10-AS1, FLJ26850, SARCC, RP11-222K16.2 and RP11-1C8.7. These lncRNAs were not previously known to be associated with PCa. One of these lncRNAs, SARCC, was previously reported to bind to the AR in renal cell carcinoma. Using a cloning strategy, SARCC was stably overexpressed in enzalutamide sensitive cells resulting in increased resistance to enzalutamide, thus suggesting a functional role for SARCC in enzalutamide resistance. Five mRNAs were also validated by qPCR as being significantly overexpressed in enzalutamide resistant PCa cells - CTAG1B, PEG10, SPINK1, PITX2 and PCDH7. The reported functions of the proteins encoded by these 5 mRNAs offer possible mechanisms for how resistance to enzalutamide could develop, such as modulating AR signalling and affecting neuroendocrine differentiation. This is the first time that an association with enzalutamide resistance has been reported for these mRNAs. In conclusion, this study contributed significantly to the understanding of the development of resistance in PCa by identifying a number of previously unknown lncRNAs and mRNAs associated with enzalutamide resistance. This information could provide the basis for further investigative work into potential treatment targets. It could also form the basis for a biomarker test predicting the development of resistance to enzalutamide or helping to stratify patients based on their likelihood to respond to therapy.
APPROVED
Keywords: Prostate; Cancer; Enzalutamide; Resistance; Molecular